"My Name Is Bond. Green Bond." Informational Efficiency of Climate Finance Markets - Marc Gronwald; Sania Wadud (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper investigates the informational efficiency of green bond markets using a recently introduced quantitative measure for market inefficiency. The methodology assesses the deviation of observed asset price behavior from the Random Walk benchmark, which represents an efficient market. The main findings of the analysis are as follows: the degree of informational inefficiency of the green bond market is generally found to be very similar to that of benchmark bond markets such as treasury bond markets. For extensive periods, what is more, it is even found to be less inefficient. Overall, the price developments in green bond markets are very similar to those in the benchmark bond markets. In other words, fundamental factors that drive bond prices in general also drive prices for green bonds. It is worth pointing out, however, that the degree of inefficiency of the green bond market during the Covid outbreak in 2020 and the inflation shock in 2022/2023 is lower than that of the treasury bond market.
Keywords: C22; E30; G14; Q02; Q31; 330; green bonds; efficient market hypothesis; fractional integration